SISTEM MANAJEMEN ASET SEBAGAI OPTIMALISASI PENELUSURAN ASET DENGAN METODE ANALYTICAL HIERARCHY PROCESS - Akrim Teguh Suseno; Abdul Razak Naufal; Devi Astri Nawangnugraeni (Politeknik Bisnis Indonesia, 2021)
Assets are one of the supporting equipment for business processes in a higher education organization. Asset management requires a system that is organized systematically so that the tracing process becomes more effective and efficient. In this case, asset management can be implemented in a web-based information system. The development of web-based asset management information system is carried out using the waterfall method, and for decision making in asset procurement priorities using the Analytical Hierarchy Process (AHP) method. The system development process uses the Codeigniter framework based on PHP and MySQL. The result of this development is a web-based asset management information system that is used to optimize asset tracking which is implemented at ITS NU Pekalongan.